Self-induced Q-switched fiber laser using tantalum aluminum carbide as a passive modulator - Ab Rahman, Mohd Fauzi; Anuar, Shairazi Akmal; Mohd Nasir, Amal Muaz; Abdul Latiff, Anas; Mohd Rusdi, Muhammad Farid; Wadi Harun, Sulaiman (Institute of Physics, 2023)
A self-induced Q-switched erbium-doped fiber laser operating at 1563 nm was achieved by integrating a passive modulator based on tantalum aluminum carbide (Ta2AlC) MAX phase film embedded into polyynyl alcohol. The modulator, serving as a saturable absorber (SA), established a modulation depth of 9% and a saturation intensity of 0.3 MW cm−2. Upon integration of the film SA, a stable Q-switched fiber laser was obtained, generating pulses with a minimum width of 7.6 µs at a repetition rate of 45.1 kHz, within a pump power range of 24.9–59.7 mW. The corresponding maximum average output power, maximum pulse energy, and highest peak power were determined at 1.6 mW, 36.2 nJ, and 4.7 mW, respectively. The RF fundamental spectrum exhibited a good signal-to-noise ratio of 61 dB, indicating excellent pulse signal quality. This demonstration of Ta2AlC MAX phase film Q-switched laser may open promising possibilities for scientific applications such as material processing.